Καὶ μὴ εἰσενέγκῃς ἡμᾶς εἰς πειρασμόν: A Lexico-Syntactical Analysis of Matthew 6:13a - Ebenezer Quaye; Jonathan Edward Tetteh Kuwornu-Adjaottor (E-Journal of Religious and Theological Studies)
The Prayer of the Lord, commonly referred to as the Lord’s Prayer in both the Matthean and Lukan accounts has received much scholarly attention over the centuries. As much as it is one of the portions of scripture usually recited by Christians especially, there are some positing challenges that need attention. Although several works have been done on it in addressing certain teething issues, it still remains one of the perceived passages of scholarly interest. In this paper, an attempt is made to resolve the issue of why Jesus Christ should ask the Father not to lead us into temptation – Καὶ μὴ εἰσενέγκῃς ἡμᾶς εἰς πειρασμόν. This study ascertained whether the Father does lead into temptation and Jesus’ request was asking for a prohibition/stoppage or whether the Father never did and that the request is asking Him not to start. By a lexico-syntactical analysis of Matthew 6:13a, it came out clearly that the author used aorist subjunctive in the prohibition, that is, μὴ εἰσενέγκῃς. This gives an emphatically strong prohibition. Since the aorist represents a punctiliar action, an action to be done without reference to its continuance or frequency; and also, as the subjunctive’s reality is uncertain, this means leading into temptation by the Father never happened and would never happen. Verily, this uncertainty of the subjunctive mood coupled with the implication of the aorist makes the eventuality of action of the verb very improbable. This paper provides an understanding of the use of the aorist subjunctive in prohibition to show its force with the negative as in μὴ εἰσενέγκῃς.